Sejarah Kedatukan Urung Sepuluh Dua Kuta Hamparan Perak Kabupaten Deli Serdang, 1823-1946 - Aini, Nur; Asari, Hasan; Zuhriah, Zuhriah (Warisan: Journal of History and Cultural Heritage, 2020)
This article discusses the history of Kedatuan Urung Sapuluh Dua Kuta Hamparan Perak. The establishment of Kedatuan Hamparan Perak originated from the migration made by Karo people. Those who originally lived in the highlands, moved to the lowlands. Some of the reasons are that the soil conditions in the lowlands are much more fertile than the highlands. In addition, in the Karo community, the king's son is required to migrate and also open a new kingdom outside of his father's power and kingdom, with the aim of making the power of their descendants be greater. This writing uses the historical writing method, with four stages, namely; heuristics, criticism or verification, interpretation and historiography. Based on the information the writer got, the arrival of the Karo people to the lowlands seemed to be welcomed by the Malays who inhabited the area. This is because there has always been a relationship between highland and lowland people, especially in terms of trade. Not only in the trade sector, but also in matters of marriage, religion and economy. Many Karo descendants are married or intermarried with Malays. During the time of the Aru Kingdom, many Karo people had settled and became residents who had embraced Islam, they married Malays. Generally, the Karo people who have settled in the lowlands have embraced Islam, the Islamization is carried out by the Malays.